Public Information Management Sustainability Priority Model With A Socio-Technical Approach and Analytic Network Process (ANP) Methods (Case Study of Salatiga City PPID) - Retnowati Retnowati; Sariyun Naja Anwar; Purwatiningtyas Purwatiningtyas (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Public information disclosure (KIP) has been mandated by law since 2008 in Indonesia, which indicates that every citizen has the right to information. This has also been done by countries that implement open government data. The implementation of KIP has not met expectations, as evidenced by the fact that not all districts/cities have information management units, there are still provinces with uninformative and uninformative status, and information disputes are still high. Obstacles such as the change of leader, the mechanism of knowledge that is shared between staff in each management unit has not been evenly distributed, also the utilization of information technology has not been optimized. The potential for the sustainability of public information management could be threatened with discontinuation. In fact, information that is easy, cheap and fast with optimal management is needed by the community. The solution offered in this research is a socio-technical approach, in which aspects of infostructure, infoculture and infrastructure. In order to find the indicators needed for each socio-technical aspect, the soft systems methodology was used, so that a conceptual model of the sustainability of public information management was built. Based on the criteria and sub-criteria indicators found, the Analytic Network Process (ANP) is used to determine the main objective of the need for sustainable management of public information. The results show that the objectives of sustainable information management are based on four priorities. The results of data processing show that from the socio-technical approach the highest priority is technology, followed by the quality of human resources and organizational culture, followed by infrastructure and information management processes. Meanwhile, the priority goals for the sustainability of public information management are firstly that information is available accurately and on time, followed by maintaining the right to public information being fulfilled, increasing public trust in the government and improving the quality of state apparatus performance.